Potential improvement in the safety and quality of traditional fermented soybean products: A narrative review - Budhi Setiawan; Nugroho Eko Wirawan Budianto; Masfufatun Masfufatun (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2022)
Soybeans are one of the most significant crops in the world due to their nutritionally valuable. It has been converted to produce a variety of fermented soybean products. During conventional soybean fermentation, microorganisms are involved, biochemical reactions occur, and bioactive components are produced. With the rise of people's living standards, customers are paying more attention not only to the flavor and nutrition of fermented soybean meals, but also to their safety and quality. Mycotoxins, biogenic amine production, and high salt content are among the public health concerns associated with fermented soybean foods. This paper reviews the prevalent concerns about the safety and quality of fermented soybean foods, as well as potential improvements. Attempts and methods have been proposed to ensure the safety of the fermentation process and food quality. Official regulations, the employment of suitable microbes, the use of high-quality cultivars, and the administration of chemicals are all viable options for improving safety and quality. We conclude that implementing international food standards, guidelines, and codes of practice such as the Codex Alimentarius for fermented soybean products and the application of scientific novel methods (e.g., starter combination, high-pressure processing, or low-dose gamma irradiation, additive usage, low salt fermentation technique) are the potential solutions to mitigate the issues and improve the safety and quality of the products.